2008
DOI: 10.1172/jci32040
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of proprotein convertases represses the metastatic potential of human colorectal tumor cells

Abstract: The proprotein convertases (PCs) are implicated in the activation of various precursor proteins that play an important role in tumor cell metastasis. Here, we report their involvement in the regulation of the metastatic potential of colorectal tumor cells. PC function in the human and murine colon carcinoma cell lines HT-29 and CT-26, respectively, was inhibited using siRNA targeting the PCs furin, PACE4, PC5, and PC7 or by overexpression of the general PC inhibitor α1-antitrypsin Portland (α1-PDX). We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 44 publications
7
118
0
Order By: Relevance
“…This should be considerd when pPC inhibitors are used in the context of cancer therapies as suggested by several laboratories, based on findings that pPCs promote tumor growth and metastasis (52). However, we note that PC7 could also protect tumors from NK cell-mediated attack by securing high MHC I levels despite low TAP or tapasin function in malignant cells.…”
Section: Discussionmentioning
confidence: 79%
“…This should be considerd when pPC inhibitors are used in the context of cancer therapies as suggested by several laboratories, based on findings that pPCs promote tumor growth and metastasis (52). However, we note that PC7 could also protect tumors from NK cell-mediated attack by securing high MHC I levels despite low TAP or tapasin function in malignant cells.…”
Section: Discussionmentioning
confidence: 79%
“…Members of the proprotein convertase family, including furin, cleave various proteins at RXKR, RXRR, RR, and KR sequences (23). HUVECs were cotransfected with plasmids encoding ANGPTL4 and ␣1-anti-trypsin Portland (␣1-PDX), a potent inhibitor of all proprotein convertases (24). We demonstrated that ␣1-PDX was efficiently transfected (green fluorescent protein expression from pIRES2-EGFP plasmid encoding ␣1-PDX; data not shown).…”
Section: Proprotein Convertases Are Involved In the Proteolytic Procementioning
confidence: 97%
“…The primary mechanism for prorenin activation has been considered to be through cleavage by prohormone convertases (Benjannet et al 1992), which may be highly expressed in cancer, including breast tumours, and this is associated with greater oestrogen dependency (Cheng et al 1997(Cheng et al , 2001). Of course, prohormone convertases may be involved in tumorigenic processes that do not involve either prorenin or angiotensin II (Siegfried et al 2003, Scamuffa et al 2008. Alternatively, the discovery of a specific prorenin receptor that binds prorenin and activates intracellular signalling pathways while at the same time activating its enzymic activity in the absence of cleavage opens new possibilities (Nguyen & Contrepas 2008, Nguyen 2011.…”
Section: Localisation Of Ras Componentsmentioning
confidence: 99%